2004
DOI: 10.1111/j.1467-9841.2004.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting perceptual cues used for the ethnic labeling of African American and European American voices

Abstract: A review of speech identi¢cation studies examining the abilities of listeners to distinguish African American and European American voices shows that Americans can recognize many African American voices with a high degree of accuracy even in the absence of stereotypical morphosyntactic and lexical features. Experiments to determine what cues listeners use to distinguish ethnicity have not yielded such consistent results, perhaps suggesting that listeners may access a wide variety of cues if necessary. An exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 50 publications
5
78
1
Order By: Relevance
“…This is made easier by the fact that all communications happen in English which means that subjects are able to hear the accent with which an individual speaks English. Numerous studies have investigated the identifiability of racial background in the presence of audial stimuli and invariably find that evaluators can recognise the ethnolinguistic differences in English with a high degree of accuracy (Purnell et al, 1999;Thomas and Reaser, 2004;Newman and Wu, 2011). In a recent (unpublished) study by Yagman (2014), third party evaluators were asked to judge whether subjects in a trust game at the same University in South Africa were mother-tongue English speakers or not, based on a short voice recording.…”
Section: Discussionmentioning
confidence: 99%
“…This is made easier by the fact that all communications happen in English which means that subjects are able to hear the accent with which an individual speaks English. Numerous studies have investigated the identifiability of racial background in the presence of audial stimuli and invariably find that evaluators can recognise the ethnolinguistic differences in English with a high degree of accuracy (Purnell et al, 1999;Thomas and Reaser, 2004;Newman and Wu, 2011). In a recent (unpublished) study by Yagman (2014), third party evaluators were asked to judge whether subjects in a trust game at the same University in South Africa were mother-tongue English speakers or not, based on a short voice recording.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, linguistic studies have also found that (18) African Americans displayed greater local F0 variation (jitter) and local amplitude variation (shimmer) than European Americans (Walton and Orlikoff, 1994); (19) African American men exhibited a greater F0 range within stress feet and lower minimum and overall F0 values than European American cohorts (Hollien and Malcik, 1962;Hudson and Holbrook, 1981;Hawkins, 1993;Walton and Orlikoff, 1994;Cole et al, 2008); (20) African Americans exhibit a lower degree of nasality than European Americans (Thomas, 2007); and (21) African American men exhibit more ''breathiness'' and less ''creakiness'' in their speech than European American men (Thomas and Reaser, 2004). Further, although speakers of many dialects will tend to simplify consonant clusters and delete a stop when the following word begins with a consonant (e.g., as in pas' the house), (22) deletion of a stop when the following word begins with a vowel (e.g., as in pas' a house) occurs more frequently in AAVE than any other European American dialect at any social level (Labov et al, 1968;Wolfram, 1969;Fasold and Wolfram, 1970;Labov, 1972a;Baugh, 1983;Miller, 1986;Butters and Nix, 1986;Pederson et al, 1986Pederson et al, -1992Gordon, 2000;Wolfram and Thomas, 2002).…”
Section: Social Stratification and The Basis For Out-group Derogationmentioning
confidence: 95%
“…If the presence of a variable results in greater accuracy in identifying some social characteristic of a model speaker than another variable, then the first is more salient than the second within the particular context of identification. 2 For example, some studies test listeners' abilities to accurately identify speaker ethnicity based on the presence of particular linguistic variables (Graff et al, 1986;Thomas and Reaser, 2004;Torbert, 2004Torbert, , 2010. Others look at identifying regional dialect or foreign accents (Boughton, 2006;Clopper and Pisoni, 2004;Fridland et al, 2004;Torbert, 2004Torbert, , 2010MacLeod, 2012;van Bezooijen and Gooskens, 1999;Williams et al, 1999).…”
Section: The Experimental Approach To Saliencementioning
confidence: 99%